2016
DOI: 10.1093/carcin/bgw113
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts regulate keratinocyte cell–cell adhesion via TGF-β-dependent pathways in genotype-specific oral cancer

Abstract: The interrelationship between malignant epithelium and the underlying stroma is of fundamental importance in tumour development and progression. In the present study, we used cancer-associated fibroblasts (CAFs) derived from genetically unstable oral squamous cell carcinomas (GU-OSCC), tumours that are characterized by the loss of genes such as TP53 and p16 and with extensive loss of heterozygosity, together with CAFs from their more genetically stable (GS) counterparts that have wild-type TP53 and p16 and min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…It is targeted by miR-141-3p which was downregulated in our data. It is suggested that the ability of OSCC cells to secrete TGF-β2 could contribute to clinical progression by maintaining a microenvironment conducive for tumor growth and proliferation 53 , 54 . In addition to the proteins discussed above we have identified a number of proteins which were overexpressed in smoke exposed cells and inversely correlated to their respective miRNAs, but have not been reported in literature in the context of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is targeted by miR-141-3p which was downregulated in our data. It is suggested that the ability of OSCC cells to secrete TGF-β2 could contribute to clinical progression by maintaining a microenvironment conducive for tumor growth and proliferation 53 , 54 . In addition to the proteins discussed above we have identified a number of proteins which were overexpressed in smoke exposed cells and inversely correlated to their respective miRNAs, but have not been reported in literature in the context of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of TGFβ on transcription can be positive or negative depending on the targeted gene and the cellular context [ 27 ]. Cirillo et al [ 28 ] suggested that the TGF-β family of cytokines secreted by cancer-associated fibroblast (CAFs) derived from genetically unstable oral squamous cell carcinomas promote the malignant phenotype by weakening intercellular epithelial adhesion. As shown by authors, members of the TGF-β family of cytokines distinguish CAFs from oral cancer and from normal oral fibroblasts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cirillo et al [ 28 ] suggested that the TGF-β family of cytokines secreted by cancer-associated fibroblast (CAFs) derived from genetically unstable oral squamous cell carcinomas promote the malignant phenotype by weakening intercellular epithelial adhesion. As shown by authors, members of the TGF-β family of cytokines distinguish CAFs from oral cancer and from normal oral fibroblasts [ 28 ]. In other studies, the researchers investigated the role of TGF-β in the induction of fibrosis in another oral disorder, namely oral submucous fibrosis (OSF) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among different signaling pathways, the Transforming growth factor βs (TGFβs) have profound effects on EMT progression [ 10 , 13 , 41 , 42 ]. Therefore, identification of TGFB2 gene as a target of DDB2 in HNSCC cells is an important observation.…”
Section: Resultsmentioning
confidence: 99%
“…In GBM, TGFβ2 has been shown to play essential role in pathogenesis [ 57 ]. In one study, the paracrine function of TGFb2 has been reported in cancer-associated fibroblasts (CAFs)-induced EMT of oral keratinocytes [ 41 ]. Identification of TGFB2 as a DDB2 target is a new significant observation.…”
Section: Discussionmentioning
confidence: 99%